A imagem em movimento na cineinstalação: poética em arte e tecnologia - Bittencourt, Ceila Teresinha Bitencourt de (2017)
The research, in Visual Poetics, in the line Art and Technology, approaches the moving image and the relation of the spectator with the same. In this sense, it seeks to investigate the way in which this relationship takes place, what its implications are, having as a principle issues related to the imaginary and the creation of fragments of fictional stories in order to enhance the imagination of the spectator. The poetic production results in analog and digital animations, with reference to the literary work "The Fantastic Chocolate Factory" by Roald Dahl. The characters Willy Wonka and the children receive a personal version considering their peculiar characteristics. Interferences in history are intended to foster the imagination of people by making them available to others. For the conception of these fictional fragments as well as of the artistic practice, one starts with the idea of montage, proper of the cinematographic language, favoring the involvement of the public with the film work. The presentation of the personal poetics of animation involves hybrid means typical of the artistic contemporaneity as the cineinstalation. The chapters of the dissertation deal with the theory and the practice of art happening concurrently, based on authors such as Sergei Eisenstein, Ismail Xavier, Marina Estela Graça, Alberto Lucena Júnior, Jacques Aumont, André Parente, Vilém Flusser, among others.